ANALYSIS OF THE INFLUENCE OF MANAGERIAL ABILITY ON HR QUALITY WITH TEACHER COMPETENCE AS AN INTERVENING VARIABLE IN LABUHAN BATU SELATAN DISTRICT - Zuhri Aulia; Pristiyono Pristiyono; Pitriyani Pitriyani (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Individual teachers with a family attitude also need expertise in classroom management so that learning takes place according to predetermined rules. This is referred to as the quality of human resources and managerial abilities as well as the teacher's competency assessment. The type of research used in this research is quantitative research. The population of this study was 3904 individuals and the sample used was selected using the Slovin formula as many as 100 individuals. The data analysis method used in this research is the component or variance structural equation model, using Partial Least Square (Smart-PLS) version 3.0 for data processing. The results of the study stated that the data analysis showed that managerial ability obtained a T-statistic of 7,103> 1.96 with a P-value of 0.000. This means that managerial ability has a significant positive effect on HR quality, or H1 is accepted. Then managerial ability obtains a T-statistic value of 22,721 > 1.96 with a P-value of 0.000. This means that managerial ability has a significant effect on teacher competence, or H2 is accepted. And the quality of human resources obtained a T-statistic value of 41,808